Systemic barriers to reporting work injuries and illnesses in contexts of language barriers. Issue 2 (20th December 2022) - Premji, Stephanie; Begum, Momtaz; Medley, Alex
Abstract: Background: Workers who experience language barriers are at increased risk of work‐related injuries and illnesses and face difficulties reporting these health problems to their employer and workers' compensation. In the existing occupational health and safety literature, however, such challenges are often framed in individual‐level terms. We identify systemic barriers to reporting among injured workers who experience language barriers within the varying contexts of Ontario and Quebec, Canada. Methods: This study merges data from two qualitative studies that investigated experiences with workers' compensation and return‐to‐work, respectively, for injured workers who experience language barriers. We conducted semi‐structured interviews with 39 workers and 70 stakeholders in Ontario and Quebec. Audio recordings were transcribed and coded using NVivo software. The data was analysed thematically and iteratively. Results: Almost all workers (34/39) had filed a claim, though most had initially delayed reporting their injuries or illnesses to their employer or to workers' compensation. Workers faced several obstacles to reporting, including confusion surrounding the cause and severity of injuries and illnesses; lack of information, misinformation, and disinformation about workers' compensation; difficulties accessing and interacting with care providers; fear and insecurity linked to precarity; claim suppression by employers; negative perceptions of, and experiences with, workers' compensation; and lack of supports. Language barriers amplified each of these difficulties, resulting in significant negative impacts in economic, health, and claim areas. Conclusion: Improving the linguistic and cultural competence of organizations and their representatives is insufficient to address under‐reporting among workers who experience language barriers. Efforts to improve timely reporting must tackle the policies and practices that motivate and enable under‐reporting for workers, physicians, and employers.